The lactate dehydrogenase gene is involved in the growth and metabolism of Lacticaseibacillus paracasei and the production of fermented milk flavor substances - Fang, Sichang; Song, Xin; Cui, Liru; Bai, Jinping; Lu, Han; Wang, Shijie (Frontiers in Microbiology, 2023)
Lactate dehydrogenase (ldh) in lactic acid bacteria (LAB) is an important enzyme in the process of milk fermentation, the objective of this study was to explore the change and effects of fermented milk metabolites in mutant strains after knocking out the ldh gene of Lacticaseibacillus paracasei. The ldh mutant ∆ldh was obtained using clustered regularly interspaced short palindromic repeats (CRISPR) technology to determine fermented milk pH, titratable acidity (TA) and viable count, and find differential metabolite in different stages of fermented milk using metabolomic analysis. The results showed that the growth rate and acidification ability of the mutant strain were reduced compared with the wild type (WT) strain before the end of fermentation, and the differential metabolites showed that lactate, L-cystine, proline and intermediate metabolites of phenylalanine, tryptophan and methionine were down-regulated (P<0.05), which affected the growth initiation rate and acidification ability of the strain. At the end of fermentation (pH 4.5), the fermentation time of the mutant strain was prolonged and all the differential metabolites were up-regulated (P<0.05), including amino acids and precursors, acetyl coenzyme A and other metabolites involved in amino acid synthesis and fatty acid synthesis, which were associated with fermented milk flavor formation. In addition, riboflavin was up-regulated to promote the growth of the strain and compensate for the growth defect caused by the mutation. Our data establish a link between ldh genes in strain growth and metabolism, and provide targets for fermented milk flavor substance regulation.